Predicting post-training implementation of a parenting intervention. Issue 4 (18th December 2017) - Kerns, Suzanne E.U.; McCormick, Erin; Negrete, Andrea; Carey, Cathea; Haaland, Wren; Waller, Scott
Abstract : Purpose: While evidence-based parenting interventions (EBPIs) are proven effective at addressing numerous emotional and behavioral health challenges for children and youth, and reduce rates of child maltreatment, they are often not well implemented in the real-world settings. Even with the state-of-the art training, many practitioners do not deliver the intervention, or do so at a reduced capacity. The purpose of this paper is to examine system-contextual implementation factors that predict timely initiation of use of an EBPI (i.e. within the first six months following training). A secondary purpose is to document additional impacts of training. Design/methodology/approach: Repeated measures were used to collect predictors and the dependent variable. The relationship between participant characteristics and use of the Triple P program was estimated using exact logistic regression. Findings: The results from 37 practitioners across three communities indicated approximately 54 percent delivered the intervention with at least one family within the first six months following training. Practitioner self-efficacy immediately following training and general attitudes toward evidence-based practices were the most significant predictors of timely use of the model. The vast majority of practitioners, regardless of implementation status, generalized learning from the training to other aspects of their work. Originality/value: Prospective examination of the predictive value of implementation factors helps to refine targeted approaches to support implementation.